Effects of aquatic exercise on mood and anxiety symptoms: A systematic review and meta-analysis - Tang, Zhengyan; Wang, Ye; Liu, Jingmin; Liu, Yujie (Frontiers in Psychiatry, 2022)
Objective Exercise has beneficial effects on mood and anxiety symptoms. However, the impact of aquatic exercise on mood and anxiety symptoms has not been clearly confirmed. Therefore, this study aimed to synthesize and systematically analyze evidence available on boosting mental health through aquatic exercise. Method A systematic review and meta-analysis were conducted under the PRISMA 2020 guidelines. PubMed, BIOSIS Previews, PsycINFO, Medline, SPORTDiscus, Education Source, and Web of Science Core Collection (WoSCC) were searched in May 2022. The research included the influence of aquatic exercises on mood and anxiety symptoms. After assessing trial quality and completing data extraction, a meta-analysis was carried out through R software. The results were presented as a standardized mean difference (SMD) and the corresponding 95% confidence interval. Results A total of 18 original trials were included. People who received aquatic exercise intervention had a statistically significant reduction in mental disorder symptoms compared with before. The results were aquatic exercise [SMD = −0.77, 95% CI (−1.08, −0.47), I2 = 77%, P < 0.01], swimming [SMD = −0.51, 95% CI (−1.14, 0.12), I2 = 78%, P < 0.01], aquatic aerobics [SMD = −0.92, 95% CI (−1.32, −0.53), I2 = 78%, P < 0.01], moderate intensity [SMD = −0.75, 95% CI (−1.07, −0.43), I2 = 67%, P < 0.01], and low intensity [SMD = −1.07, 95% CI (−1.08, −0.47), I2 = 85%, P < 0.01]. Conclusion Aquatic exercise could statistically significantly improve mental health. Light aquatic aerobics probably has a better effect on mood and anxiety symptoms. However, given the number and quality of included research, verifying the aforementioned conclusions requires a larger sample of high-quality studies.